Numerical study on the smoke movement and control in main roadway for mine fires occurred in branch. (May 2023) - Zhu, Hongqing; Qu, Baolin; Wang, Jingxin; Hu, Lintao; Yao, Yongzheng; Liao, Qi
Abstract: Mine exogenous fire is the main disaster in coal mines. Owing to the complicated structure and the ventilation network, the smoke movement and control in branched roadway fires of coal mines is more complicated than that in traffic tunnel fires. In this study, the smoke backlayering length and critical velocity in a main roadway for fires that occurred in a branch were studied with varying fire locations. The results suggest that the smoke from the branch does not spread along the width centerline of the main roadway, but forms an early "snake-shaped" structure. The variation of dimensionless backlayering length with the dimensionless variable ln ( Q ˙ * 1 / 3 / V * ) is divided into two regions with different slopes by the line of L * = 1.6. Besides, branched roadway fires have a lower backlayering length and critical velocity compared to single-hole tunnel fires. These two parameters increase with decreasing the fire-node distance. Combined with dimensionless analysis and simulation results, calculation models considering fire location were proposed to estimate the smoke backlayering length and critical velocity. The credibility of prediction models is validated by comparing them with simulation results. The outcomes of the current study guide smoke control in similar-structured mine roadways and traffic tunnels.